2021
DOI: 10.1108/er-03-2020-0099
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the moderating role of culture between job characteristics and job satisfaction: a multilevel analysis of 33 countries

Abstract: PurposeThis paper aims to address how national culture moderates the relationship between job characteristics and job satisfaction.Design/methodology/approachThe authors examine the most recent data collected from the International Social Survey Programme (ISSP) in 2015 from a group of 33 countries. Hofstede's cultural model is used to represent and measure national culture.FindingsOne of the most significant findings from the authors’ two-level regression analysis is that having an interesting job contributes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 91 publications
(119 reference statements)
0
19
0
Order By: Relevance
“…Previous research has found indulgence to be moderating the impact of hedonic value and utilitarian value on behavioral intentions (Jadil et al, 2022, Lee et al, 2013. Additionally, people from indulgent culture have high desires and wants, while the people from restraint culture tightly suppress their desires and wants (Gu et al, 2021). People from indulgent culture tend to adopt new technology (Syed and Malik, 2014).…”
Section: Moderating Effect Of Culturementioning
confidence: 99%
“…Previous research has found indulgence to be moderating the impact of hedonic value and utilitarian value on behavioral intentions (Jadil et al, 2022, Lee et al, 2013. Additionally, people from indulgent culture have high desires and wants, while the people from restraint culture tightly suppress their desires and wants (Gu et al, 2021). People from indulgent culture tend to adopt new technology (Syed and Malik, 2014).…”
Section: Moderating Effect Of Culturementioning
confidence: 99%
“…Job elements that arouse interest to the employee have been ranked and rated high in the current paper. This output is on the lines of the findings of a very recent study conducted in a different context by Gu et al (2022) who concluded that interesting job has more job satisfaction in an individualistic country than in a collectivist country.…”
Section: Discussionmentioning
confidence: 58%
“…This is due to complex conditions and their interdependent nature. The research so far has clearly indicated that the approach to work depends on the cultural context, and the level of job satisfaction varies between countries and nationalities (Kristensen & Johansson, 2008;Solberg et al, 2014;Acelya & Cemal, 2016;Andrade & Westover, 2019;Gu et al, 2021). Cross-sectional research also confirms the diversity in job satisfaction between occupations (Al-Zoubi, 2012;Andrade & Westover, 2019;Törnroos et al, 2019), and proves the significant impact of contextual characteristics related to work.…”
Section: Job Satisfaction and Its Foundationsmentioning
confidence: 87%